Acceleration derived from instrumented mouthguards during heading in women's soccer with regular and 'light' soccer balls - Bentley, L.; Lauder, M. A.; Smith, N. A. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study investigated the specific types of header that occur in elite women`s football (Bentley et al., 2022). Launch speed and angle were replicated in laboratory conditions. An ntervention of reduced ball mass (0.29kg v`s 0.41kg) was investigated. Common headers ere categorised as a) slow controlling header; b) from a throw-in; c) from long-pass/cross; ) from goal kick. A custom fit Instrumented Mouthguard (Prevent Biometrics) sampled at 200Hz to gain linear and angular accelerations of the skull. Seven female players erformed 3 trials of each header, with kinematics also recorded at 1000Hz using 10 Vicon ameras. For the `light` ball intervention, peak linear velocity of the head was significantly p<0.05) reduced at all ball speeds. If `light` ball `playability` can be demonstrated, this could e a useful intervention to mitigate excessive, cumulative head impacts in female football.